ISLAM DAN KEKERASAN DALAM RUMAH TANGGA MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KDRT - Jasmani Jasmani (Institut Agama Islam Negeri Bone, 2021)
AbstractHousekeeping is a form of coexistence between a husband and wife along with their children and those who live with him as his dependents. Al-Qur'an and hadith has outlined that a family lives in harmony, whether between husband / father with a wife / mother or with their children. Delineation of the Qur'an and hadith is sometimes not working as it should. Therefore, Allah has given the legal provisions of disobedience that occurs between a husband and wife are called to nusyuz. The climax is syiqaq. The Qur'an has hinted that if nusyuz and syiqaq can not be neutralized again, then divorce can be done as an emergency exit. However, at this time, nusyuz and syiqaq translated as domestic violence and expressed as a criminal act. This is certainly different from the conception of Islam that never gave explicit stipulation that the husband or wife can report to law enforcement if their partner violence. This paper intends to explain about contemporary Islamic legal view of domestic violence according to law number 23 of 2004 on the elimination of domestic violence.